Frontal Hypoactivation During a Working Memory Task in Children With 22q11 Deletion Syndrome. (January 2017) - Harrell, Waverly; Zou, Ling; Englander, Zoe; Hooper, Stephen R.; Keshavan, Matcheri S.; Song, Allen; Shashi, Vandana
Impairments in executive function, such as working memory, are almost universal in children with chromosome 22q11.2 deletion syndrome. Delineating the neural underpinnings of these functions would enhance understanding of these impairments. In this study, children and adolescents with 22q11 deletion syndrome were compared with healthy control participants in a functional magnetic resonance imaging (MRI) study of working memory. When the 2-back condition was contrasted with the 1-back and 0-back conditions, the participants with 22q11 deletion syndrome showed lower activation in several brain areas involved in working memory—notably dorsolateral prefrontal cortex, anterior cingulate, and precuneus. This hypoactivation may be due to reduced gray matter volumes or white matter connectivity in the frontal and parietal regions, differences that have previously been documented in children with 22q11 deletion syndrome. Understanding differences in brain function will provide a foundation for future interventions to address the wide range of neurodevelopmental deficits observed in 22q11 deletion syndrome.